Using Independent Learning Log for Listening Skill Learning Among First Year University Students - Salimah, Salimah; Dewanti, Anna (FKIP - Universitas Tanjungpura, 2024)
Students freshly admitted to the English Language and Literature study program has various levels of English proficiency. To maximize their listening skills, independent learning log was administered to the students to support their learning activities outside classroom. This action research was aimed at investigating the benefits of the log for the students